Foreign exchange rate exposure of companies under dynamic regret - Oliver Entrop; Fabian U. Fuchs (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
This paper analyzes optimal hedge ratios for foreign exchange (FX) rate risk of companies. Our contribution to the literature is twofold: (i) We present a theoretical two-period regret model that allows us to analyze the determinants of the optimal hedge ratio given the outcome of past hedging decisions and future expectations. The model implies that the optimal hedge ratio depends on the past hedge ratio, the past exchange rate return, the expected exchange rate return and the skewness of its distribution, its covariance to the foreign market return, as well as the company's risk and regret aversion. (ii) We test the related model-derived hypotheses on a broad sample of US non-financial companies over the period 1995 to 2015 and find strong evidence for the model's predictions. By adding a dynamic regret approach to the hedging and FX literature we shed further light on the rationale behind selective hedging.
Keywords: F31; G15; G32; G41; 650; exchange rate exposure; regret aversion; hedging; risk aversion; derivatives